Extrinsic and intrinsic job factors - Ismail, Hussein (2014)
A number of studies have been done in North America and Europe which examined the role of intrinsic and extrinsic job factors in overall motivation and satisfaction. However, this field of research has received very small attention, if any, in the Arab region. This research explores the effects of extrinsic and intrinsic job factors on motivation and satisfaction in the country of Lebanon. A total of 100 subjects took part in the study. Results showed that while extrinsic factors have a stronger relationship with motivation and satisfaction than intrinsic factors, the latter showed a stronger effect on overall motivation when extrinsic job factors were met. Discussion and implications are presented.